Relief Candi Borobudur, Prasasti, dan Berita Asing: Visualisasi Perburuan Masa Mataram Kuno - Pradita, Dennys (Masyarakat Sejarawan Indonesia, 2020)
Relief is a sculpture on a building or stone that describes a message or event that occurred at that time. In addition to reliefs, depictions of human life during the Hindhu-Buddhist period are found in inscriptions and also records of foreigners visiting the archipelago. One side of life depicted in these three sources is the hunting of animals. Then how are the three historical sources in this classical period able to provide a visualization of life so that they can be translated as historical sources. These three sources complement each other about the visualization of hunting, scratches on the reliefs of Borobudur Temple provide a visual picture, and the inscriptions will explain the meaning and terms of hunting, and finally the more foreign news about the types of animals being traded. These historical sources are examined using the Archaeological approach to be a historiography.